2022
DOI: 10.3390/nu14224736
|View full text |Cite
|
Sign up to set email alerts
|

Subjective-Physiological Coherence during Food Consumption in Older Adults

Abstract: Background: Subjective–physiological emotional coherence is thought to be associated with enhanced well-being, and a relationship between subjective–physiological emotional coherence and superior nutritional status has been suggested in older populations. However, no study has examined subjective–physiological emotional coherence among older adults while tasting food. Accordingly, the present study compared subjective–physiological emotional coherence during food consumption among older and younger adults. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…An interesting aspect concerns the association between subjective-physiological emotional coherence and greater well-being, as well as between subjective-physiological emotional coherence and superior nutritional status, in older populations. Accordingly, the study by Saito et al [41] compared the subjective-physiological emotional coherence during food consumption between older and younger adults, by the means of facial electromyography. The results revealed that the emotional coherence between subjective experiences and the facial electromyography (EMG) activity during food consumption was maintained or increased in older adults as compared to younger ones, suggesting that the essential function of emotions is maintained in older adults, which probably enhances the quality of health and life in late adulthood.…”
mentioning
confidence: 99%
“…An interesting aspect concerns the association between subjective-physiological emotional coherence and greater well-being, as well as between subjective-physiological emotional coherence and superior nutritional status, in older populations. Accordingly, the study by Saito et al [41] compared the subjective-physiological emotional coherence during food consumption between older and younger adults, by the means of facial electromyography. The results revealed that the emotional coherence between subjective experiences and the facial electromyography (EMG) activity during food consumption was maintained or increased in older adults as compared to younger ones, suggesting that the essential function of emotions is maintained in older adults, which probably enhances the quality of health and life in late adulthood.…”
mentioning
confidence: 99%